Beyond movement: exploring the combined impact of breathing exercises and the PEPSMAN protocol on cognitive and functional recovery in knee osteoarthritis - Nandgaonkar, Gouri G.; Afle, Gauri M. (International Journal Of Community Medicine And Public Health, 2025)
Knee Osteoarthritis (KOA), a leading cause of disability globally, is linked to sedentary lifestyles, obesity, and chronic low-grade inflammation affecting joint and cognitive health. Physical exercise reduces oxidative stress and inflammation, benefiting brain health. The PEPSMAN protocol—combining patient education, exercise, and manual therapy—improves balance, pain, physical function, and reduces disability in KOA. Although limited, early evidence suggests combining PEPSMAN with breathing exercises offers additional benefits. This review synthesizes recent research on the interplay of inflammation, cognition, pain, and rehabilitation in Grade II–III KOA. A comprehensive search across databases like EMBASE, SCOPUS, DOAJ, PubMed, Google Scholar, and Web of Science identified peer-reviewed articles and clinical trials focusing on these factors in KOA.KOA progression associates with increased dementia and Alzheimer’s disease risk; chronic pain significantly contributes to cognitive decline and functional impairment. Emerging studies reveal respiration influences cognitive performance. Combining breathing exercises with PEPSMAN enhances cognition and physical function in KOA by reducing inflammation, improving autonomic regulation, and promoting neuroplasticity, addressing joint symptoms and cognitive decline in a holistic approach. Chronic low-grade inflammation is central to KOA pathophysiology, driving joint damage and neurodegeneration linked to cognitive decline and Alzheimer’s disease risk. This highlights the need for integrative management targeting musculoskeletal and neurocognitive health.